Pengaruh Kemudahan, Keamanan, dan Fitur Layanan Terhadap Minat Pelaku UMKM Dalam Menggunakan Mobile Banking Bank Syariah Indonesia di Kota Banda Aceh - Siti Humairah-DJ; Ismail Rasyid Ridla Tarigan; Ismail Nura (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The digital transformation of Islamic banking has encouraged Micro, Small, and Medium Enterprises (MSMEs) in Banda Aceh to shift from conventional transactions to mobile banking services, however, the use of mobile banking remains limited despite the availability of access and facilities. The need for efficient transactions via mobile banking is becoming increasingly urgent as the digital transformation accelerates, yet many MSMEs persist with conventional methods and believe that the applications cannot be used optimally. This study analyzes the extent to which ease of use, security levels, and service feature quality influence MSME operator’s interest in utilizing Bank Syariah Indonesia’s mobile banking services, particularly in Banda Aceh. The study will employ a quantitative approach using purposive sampling, collecting primary data through a questionnaire distributed to 100 respondents, and applying multiple analysis methods with the assistance of IBM SPSS Version 31. The results of the study show that, individually, ease of use and service features have a significant influence on the interest in using Bank Syariah Indonesia’s mobile banking. Conversely, security aspects do not show a significant influence on the interest in using the service. Collectively (simultaneously), these three variables significantly influence the interest in using Bank Syariah Indonesia’s mobile banking in Banda Aceh.